2018
DOI: 10.3389/fpsyg.2018.00697
|View full text |Cite
|
Sign up to set email alerts
|

Validity of the Parental Burnout Inventory Among Dutch Employees

Abstract: The purpose of this study was to validate the Parental Burnout Inventory (PBI) in a Dutch sample of working parents. The Dutch version of the PBI and questionnaires about work were administered to 627 working parents, with at least one child living at home. We investigated whether the tri-dimensional structure of the PBI held in a sample of male and female employed parents. Furthermore, we examined the relationships between PBI and the constructs work-related burnout, depressive mood, parenting stress and work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
59
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(69 citation statements)
references
References 43 publications
2
59
0
8
Order By: Relevance
“…Considering this, Roskam et al (2017) developed and tested a tool for measuring parental burnout, and found that 2-12% of parents in Belgium experienced such burnout. Building on this work, Van Bakel et al (2018) reported that in the Netherlands, this rate was 0.2-7.7%, while Kawamoto et al (2018) reported that it was 4.2-17.3% in Japan.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…Considering this, Roskam et al (2017) developed and tested a tool for measuring parental burnout, and found that 2-12% of parents in Belgium experienced such burnout. Building on this work, Van Bakel et al (2018) reported that in the Netherlands, this rate was 0.2-7.7%, while Kawamoto et al (2018) reported that it was 4.2-17.3% in Japan.…”
Section: Introductionmentioning
confidence: 81%
“…There has recently been considerable interest in parental burnout, and an increasing number of studies have been conducted in different countries, including the Netherlands (Van Bakel et al, 2018), Turkey (Demirhan et al, 2011), Iran (Beheshtipour et al, 2016), and India (Vinayak and Rohin Kaur, 2017). However, a recent review by Sánchez-Rodríguez et al (2019) reported that although 39 theses regarding parental burnout were published in 1989-2018, none were conducted in China or used a Chinese sample.…”
Section: Introductionmentioning
confidence: 99%
“…In accordance with our hypotheses, the total score of the PBA and its four subscales were all statistically significantly and positively associated with depressive symptoms and sleep disruptions and statistically significantly and negatively associated with self‐esteem. In other words, parents scoring high in parental burnout also reported higher levels of depressive symptoms (see also Kawamoto et al ., 2018; Mikolajczak et al ., 2019; Van Bakel et al ., 2018; Roskam et al ., 2017), sleep disruptions (see also, e.g., Lindström et al ., 2011; McQuillan et al ., 2019), and lower self‐esteem (see also Lindström et al ., 2011; Mikolajczak & Roskam, 2018). The highest correlations with criteria variables were found for depressive symptoms, which correlations were somewhat higher than those reported in previous studies (Kawamoto et al ., 2018; Mikolajczak et al , 2019; Van Bakel et al ., 2018; Roskam et al ., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, it has been argued that valid burnout measures need to positively correlate with depression (Cresswell & Eklund, 2006). The few existing studies on parental burnout have found that maternal burnout is associated with depressive symptoms, with correlations ranging from .41 to .48 (Kawamoto, Furutani & Alimardani, 2018; Mikolajczak et al ., 2019; Van Bakel, Van Engen & Peters, 2018; Roskam et al ., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Estos resultados difieren a los reportados por Roskam et al (2017) en población europea, en donde no se observaron diferencias significativas entre madres y padres respecto a su desgaste parental, aun cuando se corresponden con investigaciones más recientes en esta misma población que compararon el parental burnout entre géneros (Roskam & Mikolajczak, 2020). También difieren de investigaciones con población alemana en la cual los padres presentaron mayores niveles de burnout parental que las madres (Van Bakel, Van Engen, & Peters, 2018). Como señalan Sánchez-Rodríguez, Perier, Callahan y Séjourné (2019), las diferencias en los niveles de burnout parental entre madres y padres dependen de los roles parentales atribuidos a estos en las diferentes culturas.…”
Section: Discusión Y Conclusionesunclassified